Integrasi Intuisi Visual dan Logika Formal pada Mekanisme Sense-Making Geometri Berbasis Konflik Kognitif - Siti Rukayah; Surya Sari Fara Diba (Mandalika Mathematics and Educations Journal, 2026)
The dominance of formula memorization often constrains students’ spatial understanding. This article investigates how Meyvira, an eleventh-grade student, navigates a cognitive transition from procedural computation to qualitative geometric reasoning when confronted with a PISA-based problem. Employing a Think Aloud approach within a single-case study design, this research reveals a critical moment in which cognitive conflict stimulates the emergence of intuitive visualization as a valid proof strategy. The findings provide new insights into the mechanisms of mathematical sense-making and offer significant implications for educators in designing instruction that balances formal logic with visual intuition to foster deeper mathematical understanding.